Perkembangan Nilai Karakter Masyarakat Berdasarkan Pemikiran Muhammadiyah K.H Ahmad Dahlam dalam Pembaruan Pendidikan Islam di Indonesia - Ridho Mujahid Islahi; Muhammad Parhan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This article examines the development of character values ​​of Indonesian society based on the thoughts of Muhammadiyah K.H Ahmad Dahlan in efforts to reform Islamic education. Dahlan's thinking played a crucial role in social and educational transformation in Indonesia at the beginning of the 20th century. This article uses historical analysis based on a historical and literary analysis approach to investigate the development of the values ​​and character of Indonesian society with Muhammadiyah thinking. This article highlights K.H Ahmad Dahlan's contribution in developing character values ​​such as leadership, independence and tolerance. The implementation of these values ​​in the Islamic education curriculum in Indonesia and their impact on the social and moral development of society are also highlighted. This article aims to provide an understanding of how the thoughts of K.H Ahmad Dahlan and Muhammadiyah shaped the character values ​​of Indonesian society and their relevance in contemporary Islamic education. As a result, Muhammadiyah's thinking in building schools and internalizing values ​​in society has improved after colonialism which was carried out a long time ago.